The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages met everywhere in the same way. Medicine thrives on experiment and comparison of different ways of doing things ; uniformity of method or belief is its enemy. (6) Encouragement of a preventive and 'positive' outlook on health. All agree that the nation will not be using its doctors to the best advantage so long as they are confined so much to healing and have so little time for preventing illness. In the hospital and specialist services the pursuit of these aims will take time. There are still too many awkward and out-of-date buildings ; even the existing accommodation cannot be fully used for want of nurses and domestic workers. There are too few of many kinds of specialists, and the few there are are not always well distributed in different parts of the country. The work of the specialist has to be carried beyond the hospital doors more than in the past. Nevertheless, the Service must be run with proper regard for economy, and capital expenditure has to be kept down to a minimum. Only the most urgent schemes for the extension or repair of hospitals can be permitted. Nor is the building of comprehensive health centres possible on any scale while so great a part of our building resources has to be locked up in urgently needed houses, factories and schools. More study is also needed of the kinds of centres most worth trying out before any large-scale experiments are launched. The building and testing of health centres in action, in different forms and circumstances, in large towns and small, in suburbs and country areas, is a task for the next few years. During that time a great many, perhaps most, family doctors will continue to practise outside health centres, though various looser forms of 'grouped' practice and other means of improving the efficiency of the family doctor without comprehensive health centres may prove valuable especially in country districts. For the time being the main thing is to get the Service into good running order and to keep on improving its efficiency. All big social changes start with a certain amount of uncertainty, until people get used to the new way of doing things ; and this Service cannot be comprehensive in the fullest sense until the country is farther along the road to prosperity and a rising standard of life. The public has still to learn how to use the new facilities properly and economically ; and those who are actually running the Service have to get used to new conditions and changing needs. But if the various professions really join forces with the laymen in the organisation described in this booklet, they can carry out a progressive new deal in medical care which will redound to the benefit of all. The National Health Service represents the completion of the work which was started just over a hundred years ago with the first Public 35 21/1489